T5 Sampling Airway Mucosal Lining Fluid Identifies Roles For IL-33 and Multiple Inflammatory Pathways in Virus-Induced Asthma Exacerbations. (19th November 2012) - Jackson, DJ; Trujillo-Torralbo, M; Footitt, J; Shamji, B; del-Rosario, J; Telcian, A; Hunt, T; Hunt, D; Mallia, P; Kon, OM; Edwards, M; Westwick, J; et al.
Abstract : Rhinovirus (RV) infection is the most common cause of asthma exacerbations (AE), however mechanisms are poorly understood. Conventional sampling techniques such as bronchoalveolar lavage dilute many cytokines below limits of detection and consequently it has not been possible to measure key mediators of Th1, Th2 and Th17 pathways during virus-induced AE's . In addition, IL-33, an epithelial-derived alarmin, has recently been shown to be essential for mouse virus-induced airway hyperresponsiveness, however the relationship between IL-33 and exacerbations in human asthma remains unknown. Using the human model of experimental RV induced AE along with novel techniques to sample upper and lower airway mucosal lining fluid (MLF) we investigated the roles of IL-33 and several other prominent cytokines in virus-induced AE's. Methods: 32 mild-to-moderate asthmatics and 14 healthy subjects were inoculated nasally with RV-16. Symptom scores were recorded daily. Bronchoscopies were performed 2 weeks prior to inoculation and on d4 post-inoculation. Novel techniques to sample MLF called 'bronchosorption' and 'nasosorption' were performed. Cytokines were measured in both bronchial and nasal samples at baseline and on d4 with further nasal sampling on days 2, 3, 5, 7, 10 and 42. Results: In asthma, nasal IL-4, –5, –13, –17, –33, and IFN-γ levels were significantly increased during infection compared to baseline (all P<0.001). IL-33 and Th2 cytokines but not IFN-γ or IL-17 were increased in asthma compared to healthy subjects (P<0.01). In the asthmatic lung, relationships between bronchial IL-33 (P<0.05), IL-13 (p<0.05), IL-5 (p=0.059) and chest symptom scores were observed. Bronchial levels of these cytokines correlated with nasal levels during infection (p<0.05) whilst baseline nasal levels of Th2 cytokines correlated strongly with infection levels (p<0.001). Conclusion: Sampling MLF permits the direct measurement of previously undetectable mediators across multiple inflammatory pathways. Increased IL-33 and Th2 induction are associated with increased AE severity. IL-33 correlated strongly with Th2 cytokine levels and may represent a novel target for the treatment of virus-induced AE's. In addition, nasal Th2 inflammation correlated with bronchial levels whilst baseline levels predicted the magnitude of Th2 induction during the AE. Therefore it may be possible to use nasosorption to guide therapy with anti-IL-5 and anti-IL-13 mAb treatments.